Сучасні критерії формування інвестиційного проекту в будівництві - Скакун, Є. В. (Ways to Improve Construction Efficiency, 2014)
This paper proposes an approach to the implementation of important structural component of the selection process, algorithm analysis and action to form an attractive investment portfolio. The leading prerequisite of this approach was the issue of analysis and examination according to real investments in modern conditions.